2008
DOI: 10.1007/s00240-008-0141-9
|View full text |Cite
|
Sign up to set email alerts
|

Citraturic, alkalinizing and antioxidative effects of limeade-based regimen in nephrolithiasis patients

Abstract: Potassium citrate has long been used as a prophylactic remedy for nephrolithiasis recurrence. Lemonade consumption is also suggested as an option. We compared the efficacy of consumption of solution containing manufactured lime powder with that of potassium citrate, on the improvement of metabolic risk factors, oxidative stress and renal tubular damage in nephrolithiasis patients. Patients with kidney stone were enrolled and randomly assigned to three treatment programs for 3 month period consisting of consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…In renal stone formers a solution containing lime powder significantly increased urine citrate, potassium, and pH (Tosukhowong et al 2008 experimental M) (20).…”
Section: Lime Juicementioning
confidence: 99%
“…In renal stone formers a solution containing lime powder significantly increased urine citrate, potassium, and pH (Tosukhowong et al 2008 experimental M) (20).…”
Section: Lime Juicementioning
confidence: 99%
“…We have been investigated the clinical efficacy of lime juice and banana stem beverage as alternatives for UL treatment. We show that our inhouse limeade-based regimen, designated lime powder regimen (LPR), efficiently delivers citraturic, alkalinizing and antioxidative actions in nephrolithiasis patients [193]. Our preclinical and phase 1 clinical trial reveals that LPR inhibits COM crystal growth and attenuates oxidative stress in vitro and is capable of increasing urine citrate, pH and antioxidant capacity in healthy individuals [194].…”
Section: Oxidative Stress In Urolithiasismentioning
confidence: 92%
“…According to literature, oral doses of potassium citrate drug for treating kidney stone patients range 20-80 mEq for potassium content, and 30-110 mEq for citrate content [16][17][18][19]. Based on our research experiences and study by Ettinger et al [16], we opted to use 21 mEq potassium and 63 mEq citrate for treating Thai kidney stone patients [15,20,21].…”
mentioning
confidence: 98%
“…Additionally, lemon juice efficiently inhibited the intrarenal deposit of calcium oxalate crystals in the ethylene glycol-induced urolithic rat model [14]. We preliminarily treated 13 nephrolithiasis patients with our in-house lime powder regimen (LPR), and demonstrated that LPR effectively delivered citraturic, urine alkalinizing, and antioxidative effects [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation